OPTIMALISASI RUTE DISTRIBUSI LOGISTIK TANGGAP DARURAT BENCANA DENGAN MENGGUNAKAN ALGORITMA SAVING MATRIX (STUDI KASUS ERUPSI GUNUNG MERAPI DI KABUPATEN MAGELANG) - Muslim, Khairul; Supriyono, Tjatur (JURNAL DWIJA KUSUMA, 2025)
Disaster logistics distribution requires a system that is fast, efficient, and adaptive. This study aimed to examine the effectiveness of the Saving Matrix algorithm in optimizing relief distribution routes during emergency operations of the Merapi eruption in Magelang Regency. The method employed was a comparative study between conventional distribution routes and routes generated through the Saving Matrix algorithm, using secondary data including distance, vehicle capacity, and terrain risk index. The findings revealed that the Saving Matrix algorithm reduced travel distance by more than 20% and accelerated distribution time. Moreover, the algorithm showed flexibility in adjusting to dynamic terrain conditions. This research concludes that the Saving Matrix method is not only theoretically relevant in the context of the Vehicle Routing Problem (VRP) but also practically applicable in disaster logistics distribution systems requiring high efficiency.